La educación transforma - González Sarmiento, Olga (2012)
The present article studies the contribution ofeducation in the lives of people, especially women,citing interesting statistics that reflect clearly thedifference in the life of someone who has beeneducated and who could not access that benefit.The premise that the author manages is that theeducation transforms and transforms for thebetter, but also warns that it will not provide suchtransformation if education to children, youth and/oradults receiving lacks with the minimum quality